Management and Evaluation of Drug Addiction Treatment Program of MEWA Hospital in Mombasa: A Work-in-Progress Case Study - Abdulnasir Mohamed Issa; Kennedy Mutundu (International Journal of Management and Data Analytics)
This study is a Work-in-Progress (WIP) that will analyze the role of monitoring and evaluation on drug addiction treatment program at the Muslim Education Welfare Association (MEWA) Hospital in Mombasa County. The research aims at measuring the effectiveness of the monitoring and evaluation system in post treatment interventions at MEWA Hospital. The objectives of the study is to achieve the level of drug addiction by analyzing the effectiveness of the monitoring and evaluation system in provision of counselling, and treatment. The target population are patients who undergo treatment of drugs at the said hospital, the health providers, and the officials of monitoring and evaluation who are available at the time of research. This study will measure the correlation analysis in order to highlight the relationship between the success of the project and drug addiction monitoring, provision of post-treatment care and counselling services. The study will be beneficial to a number of stakeholders including MEWA hospital, the county government of Mombasa, researchers in the field, medical practitioners who deal with drug and substance abuse, drug addicts and their supportive relatives, and the community at large.